Characteristic of preliminary breakdown preceding negative return stroke in Malaysia - Wooi, C. L. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper describes a study on the characteristics of preliminary breakdown pulses (PBPs) preceding negative return strokes. Such characterization is needed due to the lack of available data, especially for negative lightning, in Malaysia. Measurements were carried out in Johor Bahru, Malaysia in October 2014 using broadband antennas and a high resolution Picoscope. It was found that 84% of the negative return strokes (RS) were preceded by PBPs. 70% of the PBPs fit the BIL model and another 30% the BL model. The arithmetic mean of the PBP-RS interval is 13.2ms, which is about four times smaller compared to a similar measurement made during April to June, 2009. The difference may probably be due to a variation in the thundercloud formation which is dependent on the monsoon period in Malaysia. Further studies are required to characterize the PBPs and their relations with the monsoon period and with geographical region.